Applications of differential calculus in economics. A few simple examples for first-year students - Biernacki, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
First-year students usually ask whether they really need mathematics. This paper presents several simple examples applying differential calculus in microeconomics, which allow students to perceive that learning mathematics during their studies of economics does “pay off”.
Didactics of Mathematics; 2016; Nr 13 (17); s.5-12
Keywords: derivative of function of one variable and two variables; utility; elasticity